Cultural transformation of Turkic states in the system of integration organizations - Egamberdiyev, M.; Turgunbayev, I. (Journal of Oriental Studies, 2023)
This scientific article examines the main aspects of the cultural policy and modernization of Türkiye, which established close ties with the Turkic countries of Central Asia after the collapse of the USSR and helped strengthen their independence. The purpose of this article is to study and experience the implementation of these processes with the help of such organizations and higher educational institutions as the Turkic Academy, TURKSOY, TurkPA and UNESCO, the Khoja Ahmed Yasawi International Kazakh-Turkish University, the Kyrgyz-Turkish “Manas” University, the Yunus Emre Institute . Purposefully improving relations between the Turkic countries, Turkic organizations promoted the revival of common traditions, customs and arts of the Turkic peoples, showing the contribution of Turkic culture to world civilization. Educational programs, universities and institutes opened in the territories of the Turkic-speaking countries with the participation of Türkiye contributed to the exchange of knowledge about the traditions, culture, life of the Turkic peoples and increased competitiveness of present and future scientists of the Turkic world. The leading scientists of Türkiye in ethnography, history were involved in the universities of Kazakhstan. With the direct participation of TURKSOY, the Turkic-speaking countries in general and Kazakhstan in particular were able to include objects of tangible and intangible cultural heritage in the UNESCO list, where representatives of Türkiye played a big role. Thus, Kazakhstan became the first Central Asian country whose reserves were included in the UNESCO list. And the holiday "Navruz" was able to move from the category of a local event to a global event. These events made a significant contribution to the development and raised the prestige of the Turkic countries in the international arena. The materials for this article were collected from scientific publications, official websites of the mentioned organizations. Key words: cultural policy, Turkic organizations, TURKSOY, TurkPA, Turkic Council, UNESCO.